Changes induced by co-inoculation in nitrogen–carbon metabolism in cowpea under salinity stress - Santos,Alexandra de Andrade (2018)
ABSTRACT To mitigate the deleterious effects of abiotic stress, the use of plant growth-promoting bacteria along with diazotrophic bacteria has been increasing. The objectives of this study were to investigate the key enzymes related to nitrogen and carbon metabolism in the biological nitrogen fixation process and to elucidate the activities of these enzymes by the synergistic interaction between Bradyrhizobium and plant growth-promoting bacteria in the absence and presence of salt stress. Cowpea plants were cultivated under axenic conditions, inoculated with Bradyrhizobium and co-inoculated with Bradyrhizobium sp. and Actinomadura sp., Bradyrhizobium sp. and Bacillus sp., Bradyrhizobium sp. and Paenibacillus graminis, and Bradyrhizobium sp. and Streptomycessp.; the plants were also maintained in the absence (control) and presence of salt stress (50 mmolL-1 NaCl). Salinity reduced the amino acids, free ammonia, ureides, proteins and total nitrogen content in nodules and increased the levels of sucrose and soluble sugars. The co-inoculations responded differently to the activity of glutamine synthetase enzymes under salt stress, as well as glutamate synthase, glutamate dehydrogenase aminating, and acid invertase in the control and salt stress. Considering the development conditions of this experiment, co-inoculation with Bradyrhizobium sp. and Bacillus sp. in cowpea provided better symbiotic performance, mitigating the deleterious effects of salt stress.